A New Ozone Concentration Regulator - Michael David; Tay Ching En Marcus; Maslina Yaacob; Mohd Rashidi Salim; Nabihah Hussin; Mohd Haniff Ibrahim; Sevia Mahdaliza Idrus; Nor Hafizah Ngajikin; Asrul Izam Azmi (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Laboratory design of an ozoneconcentration regulator which is build on the theory of continuity equation forgas flow in parallel pipes in conjunction with the ozone elimination potentialsof an ozone destructor is presented. At an initial oxygen flow rate of 33.33 cm3s-1,ozone concentration was  generated andvaried between 429.30 parts per million (ppm) to 3826.60 ppm.  Similarly at an initial oxygen flow rate of 25cm3s-1, ozone concentration was  generated and varied between 387.30 ppm to4435.20 ppm. Effect of flow meter when the ozone concentration was set toapproximate 1000 ppm  were investigatedand reported. Fine tuning of the regulator is necessary to ensureconcentration stability for long duration experimental work. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.6952